Behind-the-border policies : assessing and addressing non-tariff measures / edited by Joseph Francois, Bernard Hoekman. - Francois, Joseph F.; Hoekman, Bernard M., 1959- (Cambridge University Press, 2019)
One feature of globalization is that barriers to international competition have come to be associated with differences in regulatory policies that increase the costs of engaging in cross-border sales. Such non-tariff measures (NTMs) have attracted growing attention from policy makers and raise important questions for policy research. This book provides a valuable overview of key issues related to NTMs and domestic regulation. It covers the classification and definition of NTMs, new sources of data on NTMs, the impacts of (different types of) NTMs, the challenges that confront efforts to reduce the negative trade effects of NTMs and what can and should be done through international cooperation to promote good practices in the design and implementation of NTMs. The contributors comprise a mix of leading trade policy experts - both academics and practitioners - and younger researchers who have specialized in the analysis of NTMs.